Therapeutic effects and mechanism of Teucrium polium in diabetes mellitus :a review article - Z. Moghimi*; Sh. Dehghan; S. Sayadi; A. Ghanbarian (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Amongst the serious metabolic disorders, diabetes mellitus (DM) is a common disease throughout the world. The excess of morbidity and mortality associated with DM and its complications emphasize the importance of new or alternative therapeutic strategies in prevention and treatment of this chronic disorder. Medicinal herbs grow vastly in Iran and are widely used for natural treatment of diseases. One of these medicinal plants, which has been recommended in Iranian folk medicine for treatment of DM since centuries ago, is Teucrium polium L. Methods: We searched the following electronic databases with use of keywords such as Teucrium polium, diabetes mellitus, insulin and mechanism in search engine such as Sciencedirect and Pubmed to identify the reports of relevant to Teucrium polium and diabetes mellitus. Results: In some studies, the hypoglycemic activity of Teucrium polium extracts was referred to the presence of flavonoids (rutin and apigenin), sterols, and volatile oils as the active constituents. Rutin has hypoglycemic effects possibly by stimulating glucose utilization in extra hepatic tissues and probably apigenin is responsible for stimulating the insulin release from pancreas. Conclusion: In recent studies Teucrium polium was known as a hypoglycemic plant but toxicologic studies and clinical trials are required to determine if Teucrium polium has the potential to be an effective and safe glucose lowering agent for diabetic patients.